Analysis of CLT in virtual efl classes during and post-pandemic in the unidad educativa Salinas Innova School research project - Figueroa Alava, Nallely Yamirleth (2023)
CLT is a method that develops the communicative skills of students through dialogues and interaction in real contexts or based on the student's experience. Different strategies, such as role plays, dynamics, dialogues, and debates, are used to learn English in situations as close as possible to reality without emphasizing grammar or vocabulary. This research aims to analyze the Communicative Language Teaching Method (CLT) used in English at "Unidad Educativa Salinas Innova School" during and after the covid-19 pandemic. It was carried out through the qualitative method and using the interview as a tool to collect information, which was applied to the five teachers in the English area of the institution. The results showed the advantages and disadvantages of using CLT during classes during the pandemic and post-pandemic, the tools they used and the teachers' experiences.